Successful Treatment of Primary Cutaneous Peripheral T-Cell Lymphoma Presenting Acquired Ichthyosis with Oral Bexarotene Monotherapy - Kayo Tanita; Taku Fujimura; Yota Sato; Takanori Hidaka; Sadanori Furudate; Yumi Kambayashi; Akira Tsukada; Akira Hashimoto; Setsuya Aiba (Case Reports in Oncology, 2017)
Acquired ichthyosis (AI) is a reactive cutaneous manifestation that can be associated with malignant hematological disease, including cutaneous T-cell lymphoma (CTCL). Since it is difficult to distinguish AI from ichthyosiform mycosis fungoides, to select the treatment for CTCL with ichthyosis-like appearance and to evaluate its efficacy is sometimes challenging. In this report, we describe a case of primary cutaneous peripheral T-cell lymphoma not otherwise specified presenting AI successfully treated with oral bexarotene. In the present case, the administration of oral bexarotene was not only effective for lymphoma cells infiltrating ulcers and nodules, but it also eliminated AI.